PENGARUH CORPORATE SOCIAL RESPONSIBILITY, RISIKO PASAR, PROFITABILITAS, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Energi Yang Terdaftar di BEI Periode 2013 - 2020) - Feby Aulia Zahara; Ludwina Harahap (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
Corporate competition is not one of the things that are foreign to the business world. All companies are competing to improve their company's performance in order to increase competitiveness in attracting potential investors to invest in their companies. One of them is by maximizing the value of the company. This research focuses on several challenges facing companies in the current economic development to increase firm value, which the principle of going concern or business sustainability Corporate Social Responsibility (CSR), Market Risk, Profitability, Firm Age, and Firm Size. This research used Energy Companies (Listed on IDX 2013 – 2020) as the population. This research used purposive sampling method, quantitative data based on Financial Statement Report and Annual Report. The research data proceed using SmartPLS 3.0 application. The results of this research show that CSR has a negative effect on firm value, market risk has no significant effect on firm value, profitability has a significant effect on firm value, firm age has no significant effect on firm value, and firm size has a significant effect on firm value.